KELAYAKAN USAHA PEMBUKAAN CABANG TOKO CAT ANEKA RAGAM - Daniel Surya Santoso (Jurnal Riset Manajemen dan Bisnis, 2014)
In the era of business competition is tight, Toko Cat Aneka Ragam diverse want to expand the distribution under by opening a branch for the first time in the complex Batununggal. But there are some problems in opening of the branch of this business capital needs as big enough and there is the risk of business. Needed the planning stage so that the opening of the branch will be having the risk that minimum, are required of a feasibility study which includes the aspect of the market, marketing, technical, and financial. Based on the analysis of every aspect of the feasibility of business, all aspect of meet the eligibility criteria expressed. Several recommendations that can be given is ready to add a fleet of rapid delivery to delivery of services can always maintained. It also must be more attention the issue of price increases, because before raise the price must monitor the price of the competitor first. Keywords : Feasibility Study, Market, Marketing, Technical, Financial